A systematic literature review of individual predictors on internet entrepreneurial ventures among academics - Rico Saktiawan Jang Jaya; Abu Hanifah Ayob; Zafir Khan Mohamed Makhbul; Wan Mohd Hirwani Wan Hussain (Penerbit Universiti Kebangsaan Malaysia, 2023)
The influence of university lecturers who teach, but do not practice, entrepreneurship is an important question facing academic entrepreneurship. Current literature lacks discussions regarding important predictors for becoming an entrepreneur, especially among lecturers. Because technological developments make it possible for a lecturer to become an internet entrepreneur, this study conducted a systematic literature review of articles related to identifying individual predictors that can affect internet entrepreneurial ventures among academics. Thirty-five articles published between 2012 and 2022 and sourced from the Clarivate Web of Science are summarized, reviewed, and synthesized. The findings show that human capital, social capital, and internet competence are important individual predictors that influence internet entrepreneurial ventures among lecturers. This study also proposes the use of a new fourth variable, academic internet entrepreneurial self-efficacy, to explain the phenomenon of academic internet entrepreneurship among lecturers. This study contributes to the understanding of individual predictors that influence internet entrepreneurial ventures among academics and whether lecturers can act as educators and entrepreneurs at the same time. Therefore, it is important for lecturers to develop their entrepreneurial skills both in theory and practice.